Project evaluation SOU-estuTUtor: mentors’ perception - García García, Mercedes; Carpintero Molina, Elvira; Biencinto López, Chantal; Níñez del Rio, Mª Cristina (Revista Complutense de Educación, 2014)
The introduction of new degrees in the Faculty of Education and the relevance of educational guidance comes to them, as a compulsory subject in all four grades started from 2009-2010, gives the opportunity to return and boost the University Guidance Service (UGS) as a means of consistency with the profile of their education and professional development of its students. The aim of the paper focuses on the evaluation of the results after the first year of implementing a peer mentoring project, SOU-estuTUtor Project, developed from UGS with all degree students of the Faculty of Education for Students new entrants. Program has been evaluated through the perception and satisfaction of the mentors on the organization, training, skills developed and adapted to the needs of students. After one academic year of implementation, the results show, on the one hand, the satisfaction and commitment of those involved and the partial response to the needs of the students served, as well as the optimization of the personal resources of the university but also some limitations that make it necessary to review the mentoring program in terms of control and duration of the process.